Persistent Burden of Tobacco-Related Cancers in Northeast India: A Multidimensional Analysis and Strategic Recommendations - Pallathadka, Harikumar; Roy, Parag Deb (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Despite the implementation of the National Tobacco Control Programme (NTCP), the incidence of tobacco-related cancers in Northeast India remains disproportionately high. This comprehensive study investigates the continued prevalence of tobacco-related cancers in the eight northeastern states of India, where these malignancies account for over 50% of all cancer cases, significantly exceeding the national average of 33.3%. Through a mixed-methods approach combining quantitative analysis of epidemiological data and qualitative assessment of sociocultural determinants, this research provides a multidimensional analysis of the tobacco epidemic in the region. We present a systematic evaluation of the National Tobacco Control Programme implementation, identifying critical gaps in policy execution, resource allocation, healthcare infrastructure, and sociocultural integration. Our statistical analyses demonstrate significant associations between tobacco consumption patterns and cancer incidence rates, with regression models showing strong correlations (R² = 0.76). This paper offers evidence-based strategic recommendations, including region-specific policy reforms, technologically enhanced surveillance mechanisms, culturally sensitive interventions, and economic rehabilitation measures. These findings provide a robust framework for policymakers, healthcare administrators, and community stakeholders to address this public health crisis through targeted, sustainable, and measurable initiatives.